Comparison of Percutaneous Endoscopic Lumbar Discectomy and Open Lumbar Surgery for Adjacent Segment Degeneration and Recurrent Disc Herniation. (10th March 2015) - Chen, Huan-Chieh; Lee, Chih-Hsun; Wei, Li; Lui, Tai-Ngar; Lin, Tien-Jen
Abstract : Objective . The goal of the present study was to examine the clinical results of percutaneous endoscopic lumbar discectomy (PELD) and open lumbar surgery for patients with adjacent segment degeneration (ASD) and recurrence of disc herniation. Methods . From December 2011 to November 2013, we collected forty-three patients who underwent repeated lumbar surgery. These patients, either received PELD (18 patients) or repeated open lumbar surgery (25 patients), due to ASD or recurrence of disc herniation at L3-4, L4-5, or L5-S1 level, were assigned to different groups according to the surgical approaches. Clinical data were assessed and compared. Results . Mean blood loss was significantly less in the PELD group as compared to the open lumbar surgery group P < 0.0001 . Hospital stay and mean operating time were shorter significantly in the PELD group as compared to the open lumbar surgery group P < 0.0001 . Immediate postoperative pain improvement in VAS was 3.5 in the PELD group and −0.56 in the open lumbar surgery group P < 0.0001 . Conclusion . For ASD and recurrent lumbar disc herniation, PELD had more advantages over open lumbar surgery in terms of reduced blood loss, shorter hospital stay, operating time, fewer complications, and less postoperative discomfort.